32nd National Congress of Parasitology, Pune: bringing together India's parasitologists - Purkayastha, Devatrisha; Pandit, Kushankur; Upadrasta, Sindhuri; Khilari, Ajinkya; Shanmugam, Dhanasekaran; Karmodiya, Krishanpal (Trends in Parasitology, 2025)
The 32nd National Congress of Parasitology (NCP) was held in person, 3-5 October 2024, at the Indian Institute of Science Education and Research Pune (IISER Pune), jointly organized by IISER Pune; the Council of Scientific and Industrial Research - National Chemical Laboratory, Pune; and Savitribai Phule Pune University (formerly University of Pune) in association with the Indian Society for Parasitology. The conference brought together around 250 attendees from across the country and abroad, including a diverse group of researchers, clinicians, industry experts, and students. The event provided a collaborative environment for exchanging research ideas relevant to the field of parasitology. The congress emphasized the concept of One Health, a holistic approach to address parasitic infections affecting humans and animals to promote overall health and well-being. In this TrendsTalk, the organizers provide an overview of the conference proceedings, which brought together India's vast and diverse parasitology community.